Molecular Docking and ADMET Profiling of Novel Human Dipeptidyl Peptidase-IV Inhibitors of Natural Origin from Dalbergia sissoo: In Silico Prediction in Antidiabetic Potential (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
In the quest for efficient treatment for diabetes mellitus (DM), human dipeptidyl peptidase-IV (DPP-IV) inhibitors have shown potential oral antidiabetic medications. Despite their potential, many existing medications are associated with adverse effects, highlighting the need for novel and safer alternatives. Type 2 diabetes mellitus (T2DM) treatment often relies on incretin hormones (GLP-1 and GIP), which play crucial roles in metabolism, such as enhancing secretion of insulin. However, the DPP-IV enzyme deactivates these incretins, necessitating the identification of effective DPP-IV inhibitors as potential antidiabetic agents. Although synthetic inhibitors like vildagliptin, sitagliptin, and saxagliptin are available, they can have adverse effects. Conversely, several natural plants and products inhibit the DPP-IV enzyme, offering safer and effective alternatives for diabetes treatment. This research uses a multifaceted strategy involving pharmacokinetic/toxicity assessment and in-silico Molecular Docking to explore the potential of phytochemicals from Dalbergia sissoo (D. sissoo) as DPP-IV inhibitors with antidiabetic properties. An investigation of 21 specific phytoconstituents from D. sissoo using molecular docking shows that six of them have a higher binding affinity (ΔG ≥ -7.3 kcal/mol) and significantly lower inhibition constants (Ki ≤ 3.17 µM) compared to the well-established drug Vildagliptin (ΔG = -7.3 kcal/mol, Ki = 4.45 µM). Among the top-performing compounds, Sissotrin, Isocaviudin, Tectoridin, Caviunin 7-O-glucoside, Biochanin A, 6, 7-Dimethoxy-4-phenylcoumarin, Tectorigenin, Nordalbergin, 5-Hydroxy-6,7,4'-trimethoxyisoflavone, and Dalbergin, additional study utilizing pharmacophore/ADMET profiling validates their drug-like characteristics. These phytochemicals follow Lipinski's Rule of Five, showing desirable drug qualities and having high oral availability. The results indicate that phytochemicals from D.sissoo, especially the specific compounds identified, show potential as DPP-IV inhibitors. These compounds show strong in-silico properties and deserve more experimental testing, suggesting they could be safer and more efficient options for developing new antidiabetic drugs.